The „Danica” Memorial Site in national and local politics of history and culture of memory in Croatia and Koprivnica - Najbar-Agičić, Magdalena; Seničnjak, Ivana (Balcanica Posnaniensia. Acta et studia, 2024)
The „Danica” Memorial Site in national and local politics of history and culture of memory in Croatia and Koprivnica. The aim of the article is to show the evolution of the attitude of state and local authorities toward the „Danica” Memorial Site located on the place of the first former concentration and transit camp established by the Ustasha regime during World War II (1941–1942). The Memorial Site has been established in Koprivnica in the late 70s and early 80s. The former camp operated for several months in 1941, most often as a transit site for prisoners. The public and symbolic perception of this site constitutes a reflection of changes that have taken place within the historical politics and culture of memory in Croatia over several decades. On the basis of press reports and scholarly literature, steps toward the „memorialization” of the area will be analyzed, and the evolution of the official attitude of the authorities toward what happened at „Danica” during World War II will be presented. In socialist Yugoslavia the heroic struggle of the communist partisans was emphasized above all, then they were supplemented by activities commemorating civilian victims of the war. After the breakup of Yugoslavia, „Danica” was overlooked in the official discourse, the site was neglected and associated with the „unwanted” memory of the communist partisans of World War II. Work on restoring the place to collective memory was not undertaken until the 21st century.